2021
DOI: 10.1021/acs.jpcc.1c07247
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Investigation of Graphene Functionalization with Activated Carbenes and Its Application in the Sensing of Heavy Metallic Cations

Abstract: Anthropogenic activities presently generate undesirable industrial and house waste byproducts such as heavy metallic cations (HMCs), which are then often released into the environment, despite being harmful to human beings. Developing new materials that can detect and capture HMCs is therefore highly desirable for wastewater remediation, especially if using cheap starting raw materials such as carbon. To shed theoretical light in this direction, we use density functional theory simulations to study the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 37 publications
(88 reference statements)
2
32
0
Order By: Relevance
“…46 Starting from Gaussian optimized complexes, the structures were centered into a cube (10 Â 10 Â 10 Å 3 ), then the electronic density was computed and from which the different properties were derived. 47,48 CCSD(T) 49 reference energies were calculated and used to benchmark the density functionalsωB97X-D, 50 M06-2X 51 and Cam-B3LYP 52 and HF ab-initio second, and fourth-order Møller-Plesset MP2 53,54 and MP4 53,55 methods. Each functional was tested with the following basis set: cc-pVDZ, cc-pVTZ, aug-cc-pVDZ and aug-cc-pVTZ.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Starting from Gaussian optimized complexes, the structures were centered into a cube (10 Â 10 Â 10 Å 3 ), then the electronic density was computed and from which the different properties were derived. 47,48 CCSD(T) 49 reference energies were calculated and used to benchmark the density functionalsωB97X-D, 50 M06-2X 51 and Cam-B3LYP 52 and HF ab-initio second, and fourth-order Møller-Plesset MP2 53,54 and MP4 53,55 methods. Each functional was tested with the following basis set: cc-pVDZ, cc-pVTZ, aug-cc-pVDZ and aug-cc-pVTZ.…”
Section: Methodsmentioning
confidence: 99%
“…Band structure, DOS, PDOS and differences of electronic density were computed using Quantum ESPRESSO 6.1 44 using PBE functional 45 and Rappe‐Rabe‐Kaxiras‐Joannopoulos ultrasoft pseudo potentials 46 . Starting from Gaussian optimized complexes, the structures were centered into a cube (10 × 10 × 10 Å 3 ), then the electronic density was computed and from which the different properties were derived 47,48 …”
Section: Methodsmentioning
confidence: 99%
“…Cadmium (Cd) is a heavy metal with high toxicity . Wastewater and agricultural soils polluted with Cd 2+ ions have become a global issue, owing to the fact that cadmium can accumulate in organisms throughout the food chain and a serious threat to ecosystems and human health. Recently, a wide range of methods have been explored for cadmium removal from water and soils including adsorption, chemical precipitation, membrane filtration, ion exchange, electro-kinetic extraction, solidification, phytoremediation, and soil washing. However, their large-scale application is limited due to their high cost, stability, and operational difficulties in practical settings. Accordingly, adsorbent materials such as carbon-based materials, zeolites, and metal–organic frameworks remain the preferred materials for Cd 2+ capture and remediation. However, the cadmium adsorption capacity and stability of current adsorbents are still not satisfactory, motivating the search for novel adsorbents that can selectively immobilize cadmium ions with very high adsorption capacities …”
Section: Introductionmentioning
confidence: 99%
“…Graphene has been investigated extensively for gas sensing applications because of its high sensitivity to adsorbed particles, 15 which can be further improved by functionalization, 16 introducing defects, 17 or by forming composites with polymers or metal oxides. [18][19][20] It has been shown that different adsorbed molecules have a different effect on the noise spectrum of graphene, allowing to use graphene as a selective sensor.…”
Section: Introductionmentioning
confidence: 99%